Membangun Civic Literacy melalui IPS/PKn: Persepsi Guru SMA Negeri Kota Blitar terhadap Pembelajaran IPS/PKn: Building Civic Literacy through Social Studies/Civics: Perceptions of Senior High School Teachers in Blitar City towards Social Studies/Civics Learning - Minto Santoso; M Iqbal Baihaqi (ITScience (Information Technology and Science), 2025)
Strengthening civic literacy in high school students is becoming increasingly crucial in the digital era to form citizens who are legally aware, responsible, critical, and actively participate without losing their national identity. This study aims to explore the perceptions of social studies/civics teachers in Blitar City State Senior High Schools regarding the meaning of civic literacy, the level of students' civic literacy, strategies for integrating civic values ??through in-depth learning, the methods and media used, and obstacles in its development according to the dimensions of graduate profiles. The study used a qualitative phenomenological approach with a single embedded case study design, involving eight social studies/civics teachers from four state senior high schools in Blitar City, selected purposively; data were collected through in-depth semi-structured interviews, passive observation, and document analysis during September–November 2025. The results show that teachers interpret civic literacy holistically as social sensitivity and daily civic behavior through in-depth learning; students' literacy levels have increased in the courage to express opinions but are still weak in information analysis and vulnerable to hoaxes; The most effective strategies are contextual learning based on direct experience, democratic dialogue, case studies, environmental observations, local issues in Blitar, and audiovisual media;. At the same time, the main obstacles are low information literacy and minimal exploration of local issues. Strengthening civic literacy effectively through a project-based learning model that aligns with the dimensions of the graduate profile and utilizes Blitar's local potential as a